EFFECTIVENESS OF EARLY GAIT REHABILITATION (CIRCUMDUCTION GAIT CORRECTION) ON IMPROVING GAIT SPECIFIC PARAMETERS IN HEMIPARETIC PATIENTS - Victor, Pratik; G. Varadharajulu (International Journal of Psychosocial Rehabilitation, 2020)
Muscle strengthening is beneficial for improving the lower limb function of stroke patients. But the poor independent functional performance of the hemiparetic limb suggests that more consideration should be given in the planning of exercises for stroke patients. 1)To provide early gait rehabilitation to hemiparetic patients.2)To determine the effectiveness of early gait rehabilitation.3)To improve the gait specific parameters in hemiparetic patients. This experimental study included 25 subjects satisfying the inclusion and exclusion criteria. Subjects were selected Convenience Sampling method. All the subjects were given a set of Tailored Exercise Program for hemiparetic lower limb along with conventional physiotherapy. The subjects were also given Home exercises. After a training session of 6 weeks all the subjects were reassessed with the Inked Footprint Analysis, Six Minute Walk Test and EMG Analysis of lower limb muscles.All the exercises were practiced 5 days per week for a treatment session lasting not less than 1 hour with each component being performed 10 times until the 6th week. was extremely significant difference in the mean step length scores between pre and post intervention. (p<0.0001, t=16.433). very significant difference in the mean step length scores between pre and post intervention. (p<0.0001, t=8.260). extremely significant difference in the mean speed scores between pre and post intervention. (p<0.0001, t=13.290). Early gait rehabilitation with tailored traditional exercises was effective to improve certain gait parameters like step length, stride length, speed of gait, number of steps taken and the recruitment of quadriceps, hamstrings and tibialis anterior muscle of the hemiparetic lower limbs.